(untitled) - Ehrenreich, Barbara (New York, 2001)
Includes bibliographical references.; Getting ready -- Serving in Florida -- Scrubbing in Maine -- Selling in Minnesota -- Evaluation.
Keywords: Minimum wage -- United States.; Unskilled labor -- United States.; Poverty -- United States.; Mức lương cơ bản -- Hoa Kỳ; Lao động phổ thông -- Hoa Kỳ; Nghèo đói -- Hoa Kỳ